The Influence of Social Media Marketing and Electronic Word Of Mouth on Consumer Purchase Decisions of Coil Rocket Builds in Sidoarjo - Rohana, Ujang Permadi; Pudjoprastyono, Heri (Formosa Journal of Science and Technology, 2024)
This research aims to examine whether models of social media marketing and electronic word of mouth contribute to purchasing decisions for Coil Rocketbuilds products. In this research, the population is consumers who have purchased Rocket Builds brand coils and live in Sidoarjo with a sample size of 70 respondents. The data collection method in this research uses a survey method and uses partial least squares as a data analysis tool. The research results found that social media marketing and electronic word of mouth had a big impact on purchasing decisions for Coil Rocket Builds products.